DOI: 10.1007/978-1-59745-394-3_21
|View full text |Cite
|
Sign up to set email alerts
|

Studying HCV Cell Entry with HCV Pseudoparticles (HCVpp)

Abstract: HCV infection leads in 50 to 80% of cases to chronic hepatitis, liver cirrhosis, or hepatocellular carcinoma. Interferons and the nucleoside analog ribavirin form the basis for treatment but are not sufficiently effective and have numerous side effects. Although about 300 million people worldwide are estimated to be infected, the characterization of HCV biology and associated pathologies and development of new therapeutics have been slow. Systems that support HCV replication and particle formation in vitro hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The virus-containing extracellular medium was collected 48 h after transfection and separated from cell debris by passing through a 0.45-m filter. For the neutralization assay, the virus-containing medium was incubated with each HMAb at various concentrations, or with phosphate-buffered saline instead of the antibodies as an infectivity control, plus 4 g/ml Polybrene at 37°C for 60 min (4,39).The HCVpp-antibody mixture was transferred to Huh7.5 cells (8 ϫ 10 3 cells/well) preseeded in 96-well plates, and infected cultures were centrifuged at 730 ϫ g for 2 h at room temperature. After incubation at 37°C in the presence of 5% CO 2 for 15 h, the unbound virus was replaced with fresh complete medium, followed by additional incubation for a total of 72 h. For detection of HCVpp entry, 100 l of reconstituted Bright-Glo (Promega, Madison, WI) was added to each well, followed by 2 min of mixing and light detection in a Veritas microplate luminometer (Turner Biosystems, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The virus-containing extracellular medium was collected 48 h after transfection and separated from cell debris by passing through a 0.45-m filter. For the neutralization assay, the virus-containing medium was incubated with each HMAb at various concentrations, or with phosphate-buffered saline instead of the antibodies as an infectivity control, plus 4 g/ml Polybrene at 37°C for 60 min (4,39).The HCVpp-antibody mixture was transferred to Huh7.5 cells (8 ϫ 10 3 cells/well) preseeded in 96-well plates, and infected cultures were centrifuged at 730 ϫ g for 2 h at room temperature. After incubation at 37°C in the presence of 5% CO 2 for 15 h, the unbound virus was replaced with fresh complete medium, followed by additional incubation for a total of 72 h. For detection of HCVpp entry, 100 l of reconstituted Bright-Glo (Promega, Madison, WI) was added to each well, followed by 2 min of mixing and light detection in a Veritas microplate luminometer (Turner Biosystems, Sunnyvale, CA).…”
Section: Methodsmentioning
confidence: 99%
“…A comprehensive protocol for HCVpp production can be found in the review by Bartosch et Cosset [155]. Briefly, HCVpp are generally produced in human embryonic kidney (HEK) 293T cells co-transfected by three expression vectors ( Figure 2).…”
Section: Retroviral Hcv Pseudoparticles (Hcvpp): a Specific Entry Systemmentioning
confidence: 99%
“…Significant progress has been made possible with the development of HCV pseudoparticles (HCVpps), consisting of unmodified HCV E1-E2 glycoproteins assembled onto retrovirus core particles (Bartosch & Cosset, 2009;Bartosch et al, 2003a;Drummer et al, 2003;Hsu et al, 2003), and with the isolation of an infectious HCV clone able to replicate and produce virus particles in cell culture (HCVcc) (Lindenbach et al, 2005;Wakita et al, 2005;Zhong et al, 2005). HCVpps are a most convenient surrogate model for HCV, as they can be handled in a Biosafety Level 2 laboratory and their extensive characterization has shown that they closely mimic the early steps of HCV entry Helle & Dubuisson, 2008).…”
Section: Introductionmentioning
confidence: 99%